#### Answer

(a.) Hence, the point $ (-5,-6) $ satisfy $ 2x-y=-4 $.
(b.) Hence, the point $ (-5,-6) $ satisfy $ 3x-5y=15 $

#### Work Step by Step

(a.)
The given point is $ (-5,-6) $ and the equation is $ 2x-y=-4 $.
Substitute $ x=-5 $ and $ y=-6 $ into the equation.
$ 2(-5)-(-6)=-4 $
$ -10+6=-4 $
$ -4 = -4 $. Satisfied.
(b.)
The given point is $ (-5,-6) $ and the equation is $ 3x-5y=15 $.
Substitute $ x=-5 $ and $ y=-6 $ into the equation.
$ 3(-5)-5(-6)=15 $
$ -15+30=15 $
$ 15 = 15 $. Satisfied.